GIS analysis of basketball courts and healthy stores relationship for young population in the city of Sкopje - Stojanova, N.; Vignjevikj, R.; Naumoski, Andreja (IEEE, 2020)
Today we live in a world where everything that we need we can obtain from the comfort of our homes. Although this is very convenient, our physical and mental health are paying the price. Physical exercises are one of the key elements in our daily lives that keep our bodies in top shape. Therefore, in this paper we address two key health components: exercises through sport and healthy eating. For this purpose, we have mapped most of the open fields and closed basketball courts in the city of Skopje, the population numbers of young people between the age of 5 and 25, as well as the healthy food and pharmacy stores using Geographic Information Systems. Combing the information from these three sources, we obtain data fusion spatial analysis map that we use to find the best location for opening new basketball court, and in the same time providing crucial knowledge of spatial regions where young people can have healthy food or buy medicines in a case of injury.
Keywords: Geographical Information Systems, Young People, Sport, Healthy Food